Epithelial morphogenesis in the perinatal mouse uterus. Issue 11 (3rd September 2020) - Vue, Zer; Behringer, Richard R.
Abstract: Background: The uterus is the location where multiple events occur that are required for the start of new life in mammals. The adult uterus contains endometrial or uterine glands that are essential for female fertility. In the mouse, uterine glands are located in the lateral and antimesometrial regions of the uterine horn. Previous three‐dimensional (3D)‐imaging of the adult uterus, its glands, and implanting embryos has been performed by multiple groups, using fluorescent microscopy. Adenogenesis, the formation of uterine glands, initiates after birth. Recently, we created a 3D‐staging system of mouse uterine gland development at postnatal time points, using light sheet fluorescent microscopy. Here, using a similar approach, we examine the morphological changes in the epithelium of the perinatal mouse uterus. Results: The uterine epithelium exhibits dorsoventral (mesometrial‐antimesometrial) patterning as early as 3 days after birth (P3), marked by the presence of the dorsally positioned developing uterine rail. Uterine gland buds are present beginning at P4. Novel morphological epithelial structures, including a ventral ridge and uterine segments were identified. Conclusions: The perinatal mouse uterine luminal epithelium develops dorsal‐ventral morphologies at 3 to 4 days postpartum. Between 5 and 6 days postpartum uterine epithelial folds form, defining alternating left‐right segments. Key Findings: Morphological patterning events in the perinatal uterine epithelium are not well described. Light sheet microscopy was used to generate volumetric reconstructions of the perinatal mouse uterine epithelium. At postnatal day 3 (P3), the uterine epithelium shows the first signs of dorsoventral pattern, with the presence of the forming mesometrially‐positioned uterine rail. The first morphological indication of uterine adenogenesis begins at P4. Novel morphological structures were identified from volumetric reconstructions, including the presence of a ventral ridge (another sign of dorsoventral pattern) and uterine segmentation.